Case Report: Adult Post-COVID-19 Multisystem Inflammatory Syndrome and Thrombotic Microangiopathy - Boudhabhay, Idris; Rabant, Marion; Roumenina, Lubka T.; Coupry, Louis-Marie; Poillerat, Victoria; Marchal, Armance; Frémeaux-Bacchi, Véronique; El Karoui, Khalil; Monchi, Mehran; Pourcine, Franck (Frontiers in Immunology, 2021)
Background: The coronavirus disease 2019 (COVID-19) pandemic has affected millions of people worldwide. A clinical series of Kawasaki-like multisystem inflammatory syndrome (MIS), occurring after SARS-CoV-2 infection, have been described in children (MIS-C) and adults (MIS-A), but the pathophysiology remains unknown. Case presentation: We describe a case of post-COVID-19 MIS-A in a 46-year-old man with biopsy-proven renal thrombotic microangiopathy (TMA). Specific complement inhibition with eculizumab was initiated promptly and led to a dramatic improvement of renal function. Conclusion: Our case suggests that that TMA could play a central role in the pathophysiology of post-COVID-19 MIS-A, making complement blockers an interesting therapeutic option.